Country of Origin, Covid-19 Vaccine and the Future of Travel: a Preliminary Study in Iran - Mirzaee, Sara; Jalalinejad, Reyhaneh; George, Babu (Anais Brasileiros de Estudos Turísticos, 2021)
Country-of-origin is one of the most crucial aspects of a brand's success. Country-of-origin has a significant impact on how brands are perceived, especially in terms of the promise of quality they deliver. While different countries have announced vaccines, there has been a global hesitation to buy into those claims. Successful adoption of a successful vaccine is critical to re-launching global travel and the leisure economy. In this article, we discuss the importance of country of origin in products getting the trust needed for them to succeed – particularly a vaccine for Covid-19. A preliminary survey was conducted among 662 Iranian social media users, directly on LinkedIn and also via a Google survey instrument. Germany merged to be the iconic symbol of quality and transparency and respondents felt confident that they would not hesitate to be subjected to a German made vaccine. Germany is globally perceived as a quality leader in high technologies and medicine and Iranians concurred with this belief. Keywords: Country of origin; Branding; Vaccine; Covid-19; Tourism; Iran.